Comprehensive microsurgical anatomy of the middle cranial fossa: Part II—neurovascular anatomy - Tayebi Meybodi, Ali; Mignucci-Jiménez, Giancarlo; Lawton, Michael T.; Liu, James K.; Preul, Mark C.; Sun, Hai (Frontiers in Surgery, 2023)
Using surgical approaches to the middle fossa, the surgeon needs to understand the relevant bony anatomy. However, s/he also needs to have a clear and sound understanding of the neural and vascular anatomy because oftentimes, the osseous anatomy (except for the optic apparatus) should be removed to expose and protect the neurovascular anatomy. This is the second of a two-part article discussing the neurovascular anatomy of the middle cranial fossa. A brief discussion of the surgical approaches follows.